2007
DOI: 10.1080/09578810701504461
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Poverty Dimensions of Urban Informal Sector Operators in a Developing Economy

Abstract: Rising poverty is a cause of concern for international, regional and local organisations and policy makers. A contributing factor is urbanisation and growth in the urban informal economy which has both beneficial and detrimental effects on the urban formal economy. This study utilises primary data from two cities and a town to examine the contribution of the urban informal sector to employment creation and poverty alleviation. The findings reveal a significant positive contribution of the informal sector towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Findings are presented descriptively with some qualitative data in terms of percentages to support the analysis. Only five articles employ statistical techniques to investigate any causal relations (i.e., Agadjanian, ; Hiemstra, Van de Kooy, & Frese, ; Jaffe, Carciente, & Zanoni, ; Rajagopal, ; Reddy, ). Agadjanian () uses logistic regression analysis to test the effects of vendors’ individual characteristics on their relations with other vendors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings are presented descriptively with some qualitative data in terms of percentages to support the analysis. Only five articles employ statistical techniques to investigate any causal relations (i.e., Agadjanian, ; Hiemstra, Van de Kooy, & Frese, ; Jaffe, Carciente, & Zanoni, ; Rajagopal, ; Reddy, ). Agadjanian () uses logistic regression analysis to test the effects of vendors’ individual characteristics on their relations with other vendors.…”
Section: Resultsmentioning
confidence: 99%
“…Hiemstra et al () also apply the regression technique to analyze the impact of planning methods on Vietnamese street vendors’ success. Reddy () utilizes a Probit model to find the relationship between poverty status and socioeconomic factors. Jaffe et al () test the correlation between credit demands and characteristics of vendors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of Anderson (1998) showed that although the estimated incidence of poverty in Ulanabaatar was 38 per cent in 1996, it could have been 53 per cent in the absence of income from the informal sector there. Similarly, Reddy found that there had been a significant increase in the incomes and assets of those involved in the informal sector compared to their pre-informal sector days in Fiji (Reddy, 2007). Thus, although informal sector entrepreneurship may be an expression of poverty, it may also mitigate the negative effects of poverty, as experienced by individuals.…”
Section: Discussionmentioning
confidence: 99%